2009
DOI: 10.1017/s1751731108003455
|View full text |Cite
|
Sign up to set email alerts
|

Effect of all-trans retinol on in vitro development of preimplantation buffalo embryos

Abstract: Vitamin A is a well-known antioxidant and is essential for embryonic development, growth and differentiation. Oxidative stress is involved in the etiology of defective embryo development. The present study evaluated whether the presence of all-trans retinol (0, 1, 2, 5 and 10 mM) in maturation medium or embryo culture medium would enhance the developmental competence of preimplantation buffalo embryos in vitro. In experiment I, cumulus oocytes complex were matured with varying concentrations of all-trans retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
1
2
0
1
Order By: Relevance
“…Akçay et al [1] reported similar findings about the maturation and fertilization of bovine oocytes under the effects of serum, steroid and gonadotropins. Similar findings about the effective activities of cis-retinal acids on proportion of oocytes that reached the metaphase II stage and also in vitro embryo production were reported from Spain [20] , India [21] , Iran [22] and United States [23] . Öztürkler et al [2] reported that the percentages of oocyte maturation, cleavage, 8-cell and morula stage embryos in L-ergothioneine supplemented group were significantly higher compared with the other groups.…”
Section: Discussionsupporting
confidence: 85%
“…Akçay et al [1] reported similar findings about the maturation and fertilization of bovine oocytes under the effects of serum, steroid and gonadotropins. Similar findings about the effective activities of cis-retinal acids on proportion of oocytes that reached the metaphase II stage and also in vitro embryo production were reported from Spain [20] , India [21] , Iran [22] and United States [23] . Öztürkler et al [2] reported that the percentages of oocyte maturation, cleavage, 8-cell and morula stage embryos in L-ergothioneine supplemented group were significantly higher compared with the other groups.…”
Section: Discussionsupporting
confidence: 85%
“…As shown in Table 5, t-RA has no effect on goat parthenogenetic cleavage, parthenogenetic blastocysts and total cell numbers. The formation of blastocysts and total cell numbers of buffalo (Thiyagarajan & Valivittan 2009) and bovine (Liu et al 2004) were significantly stimulated by 5 μmol/L (all-trans) retinol treated during maturation of COCs. But all-trans 65.1 ± 0.9 73.3 ± 1.4 N = number; values were the mean ± SEM; within a column, the experimental groups were compared with the control group, **Meant statistically highly significant difference (P < 0.01), *Meant statistically significant difference (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table , t ‐RA has no effect on goat parthenogenetic cleavage, parthenogenetic blastocysts and total cell numbers. The formation of blastocysts and total cell numbers of buffalo (Thiyagarajan & Valivittan ) and bovine (Liu et al . ) were significantly stimulated by 5 μmol/L ( all‐trans ) retinol treated during maturation of COCs.…”
Section: Discussionmentioning
confidence: 99%
“…Sel diinkubasi selama 24 jam, 9 kemudian diberi retinol pada media perbenihan adiposit dengan kepekatan retinol 0,1 μM, 1 μM, 10 μM. 9 Sel adiposit jumlah sekitar 5,0x10 2 12 yang menyebutkan bahwa adiposit matur dari jaringan adiposis memiliki bentuk sel bulat dengan tetesan lemak yang sangat besar, sehingga menempatkan inti sel (nukleus) dan sitoplasma di bagian tepi sel.…”
Section: -203unclassified